MENINGKATKAN PENDIDIKAN KARAKTER BERBASIS BUDAYA MENUJU SOCIETY 5.0 PADA PERGURUAN TINGGI - Jihan Fadhilah; Seftia Eka Asmara, Ajeng Bunga Putria, Salsyabina Puspita Ayu (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Along with the times, many students, especially in tertiary institutions, no longer display character as students. Politeness, manners, and morals have begun to be underestimated. So, it is important to implement multicultural education in tertiary institutions as an alternative and solution to make students with character through multicultural values. The research method used in this study is descriptive analysis by collecting various data and sources, then analyzing and systematically explaining the urgency of multicultural education in character development in the era of society 5.0 in tertiary institutions. The results of the study found that the character of students in tertiary institutions began to decline. Multicultural cultural values have been abandoned. Many students have neglected manners, manners and manners and behavior, especially towards lecturers as teachers or educators. So, through multicultural education it is expected to be able to contribute in terms of forming character which is implemented by providing good examples such as the habit of respecting others, mutual respect and giving advice if there is bad behavior